2020
DOI: 10.3390/e22070787
|View full text |Cite
|
Sign up to set email alerts
|

Decoding Analysis of Alpha Oscillation Networks on Maintaining Driver Alertness

Abstract: The countermeasure of driver fatigue is valuable for reducing the risk of accidents caused by vigilance failure during prolonged driving. Listening to the radio (RADIO) has been proven to be a relatively effective “in-car” countermeasure. However, the connectivity analysis, which can be used to investigate its alerting effect, is subject to the issue of signal mixing. In this study, we propose a novel framework based on clustering and entropy to improve the performance of the connectivity analysis to reveal th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…To compensate for the defects of attentional allocation, the alpha functional connections in the posterior brain regions (parietal-occipital) that contribute to maintaining alertness were activated, and they were negatively related to the alerting effect. 18 The hypoconnectivity in patients with BFLI meant that they more severely needed to mobilise compensatory connectivity to increase alertness. Moreover, the hypoconnectivity in the alpha band was associated with higher scores of the MMSE and digit-span backward test, confirming that it could be a compensatory mechanism for global cognition, attention or even working memory.…”
Section: Comparison Of Perceptual Processingmentioning
confidence: 99%
“…To compensate for the defects of attentional allocation, the alpha functional connections in the posterior brain regions (parietal-occipital) that contribute to maintaining alertness were activated, and they were negatively related to the alerting effect. 18 The hypoconnectivity in patients with BFLI meant that they more severely needed to mobilise compensatory connectivity to increase alertness. Moreover, the hypoconnectivity in the alpha band was associated with higher scores of the MMSE and digit-span backward test, confirming that it could be a compensatory mechanism for global cognition, attention or even working memory.…”
Section: Comparison Of Perceptual Processingmentioning
confidence: 99%
“…After the above analysis, IMF3 was selected to extract MMSE features with a scale factor of four. Studies have shown that more obvious fatigue features can be extracted from EEGs in the occipital lobe [58,59]. Therefore, the O1-and O2-channel EEG signals were selected to extract MMSE features for the two driving modes, respectively.…”
Section: Modified Multi-scale Entropy Featurementioning
confidence: 99%
“…In recent years, researchers have developed methodologies to detect or indicate the driver fatigue state prior to a collision [11][12][13]. Generally, data from three different sources have been used to classify driver fatigue or drowsiness.…”
Section: Introductionmentioning
confidence: 99%